Ugotavljanje podobe slovenske skupnosti, ki živi na območju Furlanije Julijske krajine, na svetovnem spletu - Medvešek, Mojca (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
The image of the Slovene community populating the region of the Friuli Venezia Giulia on the world wide web. The internet plays a major role in the process of shaping up of ethnic identifications, at the same time giving ground to the creation of virtual communities. The article focuses on the image of the Slovene community in Friuli Venezia Giulia (FVG) on the World Wide Web. We studied the contents appearing on the World Web, as well as the holders of the existing websites. We investigated the possibility of creation of the virtual community of Slovenes in FVG, as well as the possibility of the World Web being just a copy of the existing institutions and their functioning. We focused on the examination of the websites, created by minority members, and on the presence of the Slovene language and information concerning the Slovene community on the websites, owned by the majority. With this aim in view we checked the websites of the Italian local administration. We can conclude on the basis of this survey that Slovenians living in Italy use internet for the presentation of their community, as a means of information, for mutual cooperation, and for the promotion of the Slovene language. On the World Wide Web there are presentations of different activities and organizations of the Slovene minority, including educational institutions, cultural and sports associations, media, firms, political parties, library, theatre, personal profiles, tourist presentations, etc. However, no virtual communities appearing on the Facebook network were found. Generally speaking, the communication dimension of the minority websites seems a bit weak. The same goes for the presence of the Slovene language and contents concerning the Slovene community on the websites of the Italian local administration in the FVG region.
Keywords: Italija; Italy; narodne manjšine; zamejski Slovenci; mass media; množični mediji; Internet (računalniško omrežje)